Characterization of genomic imbalances in diffuse large B-cell lymphoma by detailed SNP-chip analysis. - Scholtysik, R.; Kreuz, M.; Hummel, M.; Rosolowski, M.; Szczepanowski, M.; Klapper, W.; Loeffler, M.; Trumper, L.; Siebert, R.; Kuppers, R. (Int J Cancer, 2015)
The pathogenesis of diffuse large B-cell lymphomas (DLBCL) is only partly understood. We analyzed 148 DLBCL by single nucleotide polymorphism (SNP)-chips to characterize genomic imbalances. Seventy-nine cases were of the germinal center B-cell like (GCB) type of DLBCL, 49 of the activated B-cell like (ABC) subtype and 20 were unclassified DLBCL. Twenty-four regions of recurrent genomic gains and 38 regions of recurrent genomic losses were identified over the whole cohort, with a median of 25 imbalances per case for ABC-DLBCL and 19 per case for GCB-DLBCL. Several recurrent copy number changes showed differential frequencies in the GCB- and ABC-DLBCL subgroups, including gains of HDAC7A predominantly in GCB-DLBCL (38% of cases) and losses of BACH2 and CASP8AP2 predominantly in ABC-DLBCL (35%), hinting at disparate pathogenetic mechanisms in these entities. Correlating gene expression and copy number revealed a strong gene dosage effect in all tumors, with 34% of probesets showing a concordant expression change in affected regions. Two new potential tumor suppressor genes emerging from the analysis, CASP3 and IL5RA, were sequenced in ten and 16 candidate cases, respectively. However, no mutations were found, pointing to a potential haploinsufficiency effect of these genes, considering their reduced expression in cases with deletions. Our study thus describes differences and similarities in the landscape of genomic aberrations in the DLBCL subgroups in a large collection of cases, confirming already known targets, but also discovering novel copy number changes with possible pathogenetic relevance.
Keywords: Cohort Studies; DNA Copy Number Variations/*genetics; Female; *Gene Expression Profiling; Gene Expression Regulation, Neoplastic; *Genomics; Humans; *Loss of Heterozygosity; Lymphoma, Large B-Cell, Diffuse/*genetics; Male; Neoplasm Recurrence, Local/*genetics; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide/*genetics; Prognosis